Mrs “Water wars”: exploring the limits of privatization in Greece’s Supreme Administrative Court case-law - Styliani Christoforidou (Cuestiones Constitucionales)
The following focuses on the jurisprudence of the Council of State (hereinafter CoS) regarding the privatization of water that has been attempted over the last decade in view of the international obligations that the country has undertaken to repay its public debt obligations. The judicial activism adopted by the CoS in the context of these cases is not necessarily reprehensible. This resistance is based on the interpretation of Articles 5 para 5 (on the individual right to health) and Article 21 para 3 of the Constitution (public health). As the comment aims to highlight the limits and conditions of the privatization of the water must be sought to another, more solid, interpretative ground.